Economic and legal approaches to balancing the development of the transport and logistics system. - Havrylyuk, Ruslana (My University, 2021)
The globalization of market relations has given impetus to the rapid development of the transport and logistics system, which has led to its imbalance. Therefore, there is a need to develop economic and legal approaches that will balance the development of this system. The purpose of the academic paper is as follows: to reveal the factors creating an imbalance in the development of the transport and logistics system and establish economic and legal aspects that balance the transport and logistics system. To achieve the goal outlined, the following methods have been used, namely: statistical analysis, element-theoretical, correlation, factor analysis, generalization and analogy. It has been established that the factors directly affecting the development of the transport and logistics system are the level of development of transport infrastructure and customs conditions. A causal relationship between investment in transport infrastructure and income from freight traffic by various types of transport in individual EU countries has been proven. It has been established that the creation of simplified conditions of customs clearance and its electronicization contributed to balancing the development of the transport and logistics system. The legal and economic approaches in balancing the transport and logistics system of individual EU countries have been highlighted, which consist in the development of general and special strategies and their financing. Along with this, they involve the adoption of legislation, providing for the development of infrastructure, the introduction of innovative technologies, and the improvement of the internal logistics network. Such network includes an information base on the cargo service provider, recipient, ease and accuracy of cargo tracking, a simplified customs clearance system, including through electronic filing of declarations, as well as attracting investments in the implementation of the legal regulations outlined.
Keywords: movement of goods; infrastructure; customs; freight; revenue